Philosophy in Art Research - Sharma, Yam Prasad (Journal of Fine Arts Campus, 2022)
Philosophy is the exploration, quest or search of truth, essence, idea or a thing that has certain value. In art research, there is a question, and we search for the answer. The answer is the essence. Ontology is the study of essence or existence. There is a method to find the truth or essence. Epistemology is the study of method or way of finding truth. What is the use or value of the truth to the researcher and the society? Does it teach or help us in our life? Does it provide us beauty and pleasure? Axiology is the study of the value of the research. There is a problem in a research area. We search for the solution of the problem. We have a method of solving the problem. The solution has certain impact on the society. The research area is explored from certain perspective. This article attempts to clarify the connection of philosophy and research methodology in the research of arts and humanities.